To solve the polynomial equation \( x^4 - 6x^3 + 8x^2 = 0 \) by factoring, we can start by factoring out the common term.
-
Factor out the common term \( x^2 \): \[ x^2(x^2 - 6x + 8) = 0 \]
-
Now we have two factors to set to zero:
- \( x^2 = 0 \)
- \( x^2 - 6x + 8 = 0 \)
-
Solve \( x^2 = 0 \):
- The solution is \( x = 0 \).
-
Now solve the quadratic equation \( x^2 - 6x + 8 = 0 \). We can factor this quadratic: \[ x^2 - 6x + 8 = (x - 2)(x - 4) = 0 \]
-
Set each factor to zero:
- \( x - 2 = 0 \) gives \( x = 2 \).
- \( x - 4 = 0 \) gives \( x = 4 \).
-
Combine all the solutions: The complete set of solutions is: \[ x = 0, 2, 4 \]
Final answer: The solutions are \( 0, 2, 4 \).
Graphical Check
To check these solutions graphically, you can plot the function \( y = x^4 - 6x^3 + 8x^2 \) and see where it intersects the x-axis. These intersection points correspond to the solutions of the polynomial equation. You'll find that the graph touches the x-axis at \( x = 0 \), \( x = 2 \), and \( x = 4 \), confirming that these are indeed the solutions.